Geophysical characterization of the in-situ CO2 mineral storage pilot site in Helguvik, Iceland - Junker, Jonas; id_orcid:0 009-0003-8630-1030; Obermann, Anne; id_orcid:0 000-0001-6933-6301; Voigt, Martin; Maurer, Hansruedi; Eruteya, Ovie Emmanuel; Moscariello, Andrea; Wiemer, Stefan; id_orcid:0 000-0002-4919-3283; Zappone, Alba Simona; id_orcid:0 000-0003-0965-7271 (Elsevier, 2025)
In-situ CO2 mineral storage is moving into focus as a technology for storing substantial amounts of CO2 that would otherwise be released into the atmosphere. However, one of the main drawbacks of this technology is that it requires large amounts of freshwater for injection. To overcome this obstacle, a pilot project in Helguvik, Iceland is testing the effectiveness of carbon mineralization using saline water, similar to seawater. Here, we describe the project and the geophysical characterization of the pilot site using crosshole seismic- and single-hole electrical resistivity measurements. The data show that the subsurface strata are dominated by decameter-thick horizontal layers of basaltic strata, with varying seismic velocities and electrical resistivities. Variations in both seismic velocity and electrical resistivity are in excellent agreement and delineate high and low porosity zones in the subsurface. The results are compared to well logging results and the mineralogical composition of drill cuttings to build a comprehensive subsurface model of the future CO2 mineral storage reservoir, highlighting potential pathways for the injected CO2-charged waters. ISSN:1750-5836 ISSN:1878-0148